2019
DOI: 10.1016/j.jclepro.2019.01.142
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable production of pure silica from rice husk waste in Kazakhstan

Abstract:  Rice husk-an agricultural waste was successfully converted into pure amorphous silica;  Three different locally grown samples of rice hull were utilized for silica extraction; 2  Three different methods for the production of silica from rice husks were investigated;  A greener and more economic method gave promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(91 citation statements)
references
References 30 publications
7
69
0
3
Order By: Relevance
“…Therefore, RHA can be a potential source for production of silica that not only reduce the dependency of extraction of silica from virgin resources, like quartz, granite, and gravel sand stone, but also solve the disposal problem of waste materials . This silica is reported to be used for production of silicon‐based material such as concrete, laboratory glass wares, absorbents silicon carbide, silicon nitride, and zeolites . Silica extracted from RHA can also be used for production of metallurgical grade silicon (MG‐Si) and solar grade silicon (purity level equivalent to 99.99% and 99.9999%, respectively) reported by several authors …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, RHA can be a potential source for production of silica that not only reduce the dependency of extraction of silica from virgin resources, like quartz, granite, and gravel sand stone, but also solve the disposal problem of waste materials . This silica is reported to be used for production of silicon‐based material such as concrete, laboratory glass wares, absorbents silicon carbide, silicon nitride, and zeolites . Silica extracted from RHA can also be used for production of metallurgical grade silicon (MG‐Si) and solar grade silicon (purity level equivalent to 99.99% and 99.9999%, respectively) reported by several authors …”
Section: Introductionmentioning
confidence: 99%
“…The same authors also reported that efficiency of removal of impurities diminished with increase in HCl acid concentration. For alkaline‐SiO 2 separation process, NaOH was mostly preferred for extraction of silica with purity level above 95% . However, due to high cost of NaOH, few researchers have used carbonate like Na 2 CO 3 for extraction of silica from RHA and found comparative results .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The moisture content of rice husk is higher than OPEFB. The hygroscopic behavior of rice husk is related to the high content of silica [29]. The ash content of rice husk is also much higher than OPEFB, where some reports showed that rice husk substantially had ash content higher than 15 % and the major component is silica compound.…”
Section: Results and Discussion 31 Characterization Of Rice Husk Anmentioning
confidence: 99%